Sistem Informasi Pengarsipan Surat Masuk dan Keluar dengan Algoritma Sequential Search di Kelurahan Bahagia - Mugiarso; Tri Furkan Sarjono Aji; Khairunnisa Fadhilla Ramdhania (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
In Kelurahan Bahagia, there are problems in managing archives, especially archiving incoming and outgoing letters, precisely in the search and presentation of mail information, often experiencing delays and difficulties in finding the archives of the letters. This study aims to assist Kelurahan Bahagia in overcoming the problem of mail archives, by designing and developing an information system for archiving incoming and outgoing mail using the Rapid Applciation Development (RAD) method and using a sequential search algorithm to help find mail information faster and easier. The result of this research is an information system for archiving incoming and outgoing mail that can help overcome the problem of filing letters in Kelurahan Bahagia.